Research Note: The Sources of Public Feelings towards Religious Groups in Britain: The Role of Social Factors, Religious Characteristics, and Political Attitudes - Clements, Ben (Journal of contemporary religion, 2012)
This research note examines public feelings towards religious groups in Britain, using thermometer scores from nationally representative survey data. It first examines whether there are significant differences in feelings by religious characteristics. It then assesses the role of religious factors in a series of regression models accounting for social factors and political attitudes. There are common factors underlying less positive feelings towards religious groups. These include being male, holding no or lower-level qualifications, supporting a minor political party or having no partisan attachment, and lower levels of political engagement. Age, religious affiliation, personal importance of religion, and ideological beliefs show a more complex set of relationships with feelings towards religious groups.